2021
DOI: 10.7759/cureus.13471
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Elevated Body Mass Index and Its Association With Non-Communicable Diseases in Patients Presenting to an Endocrinology Clinic

Abstract: Introduction In the last 45 years, the worldwide rate of obesity has risen by nearly three-folds. Globally, 650 million adults are obese and more than 1.9 billion are overweight. The estimated prevalence of overweight and obesity in Pakistan was found to be 25% and obesity prevalence alone was 10.3% using the Asian-specific body mass index (BMI) criteria. According to the World Health Organization, overweight and obesity increase the risk of non-communicable diseases (NCDs). Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The Institutional Review Board Committee granted the ethical approval.The sample size was calculated using the WHO sample size calculation using the population prevalence of raised BMI in hypertensive patients as 72.6%. 11 Non probability consecutive sampling was used to gather the sample. Inclusion criteria: All patients aged 18 and 65 who managed hypertension with BMI>25 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The Institutional Review Board Committee granted the ethical approval.The sample size was calculated using the WHO sample size calculation using the population prevalence of raised BMI in hypertensive patients as 72.6%. 11 Non probability consecutive sampling was used to gather the sample. Inclusion criteria: All patients aged 18 and 65 who managed hypertension with BMI>25 were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…World Health Organization has reported that overweight and obesity increase the risk of non-communicable diseases. In the past 45 years, the rate of increase in obesity has tripled worldwide, with 1.9 billion adults aged 18 years or above being overweight and 650 million classified as obese ( Ghaus et al, 2021 ). Obesity is associated with a high risk of morbidity, disability, and death, with mortality risk similar to that of smoking ( Whitlock et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%